Edukasi Kesehatan tentang Faktor Risiko Kesehatan pada Bayi dengan Post Perawatan Diare untuk Mengatasi Defisit Pengetahuan Ibu: Health Education on Risk Factors in Infants Post-Diarrhea Care to Manage Mother’s Knowledge - Eka Sofiana Putri Eka; Eka Adimayanti (Universitas Ngudi Waluyo, 2026)
Diarrhea in infants is a condition when bowel movements occur more than 4 times with liquid stool consistency within 24 hours. The post-treatment period of diarrhea in infants is a condition that requires more understanding for new mothers who have no experience in caring for babies, because it can lead to the risk of recurrent diarrhea. Therefore, health education on diarrhea prevention is needed. This health education was conducted for three consecutive days to assess the knowledge gained. The education was given to one respondent with a knowledge deficit regarding risk factors for infant health after diarrhea treatment. This method used the nursing care process with data collection through interviews, observation, physical examination, documentation, and management. Before health education, to assess the level of knowledge, the author used a demonstration technique by asking several questions about diarrhea. The final outcome of this case management is that the patient's mother was able to explain and apply diarrhea prevention strategies. Based on the nursing interventions carried out, it can be concluded that the knowledge deficit problem in mothers with infants in the post-diarrhea treatment period was resolved.